The SAGE handbook of mental health and illness - Pilgrim, David, 1950-; Pescosolido, Bernice A.; Rogers, Anne. (Los Angeles : SAGE, 2011)
This title integrates the conceptual, empirical and evidence-based threads of mental health as an area of study, research and practice. It approaches mental health from two perspectives - firstly as a positive state of well-being and secondly as psychological difference or abnormality in its social context.
Section 1 Mental health and mental disorder in social context -- The limits to psychiatric and behavioral genetics / Angus Clarke -- The challenge of measurement of mental disorder in community surveys / Jerome C. Wakefield and Mark F. Schmitz -- Mental health, positive psychology and the sociology of the self / Benedikt Rogge -- Sociological aspects of the emotions / Gillian Bendelow -- Ethnicity, race and mental disorder in the UK / James Nazroo and Karen Iley -- Gender matters: differences in depression between women and men / Jane M. Ussher -- The diagnosis of depression in an international context / Renata Kokanovic -- Stressors and experienced stress / Susan Roxburgh -- Religious beliefs and mental health: applications and extensions of the stress process model / Scott Schieman -- Children, culture, and mental illness: public knowledge and stigma toward childhood problems / Brea Perry and Bernice A. Pescosolido -- Stigma and mental disorder / Graham Scambler -- Medicalization and mental health: the critique of medical expansion, and a consideration of how markets, national states, and citizens matters / Sigrun Olafsdottir -- Danger and diagnosed mental disorder / David Pilgrim and Anne Rogers -- Section 2 Clinical and policy topics -- Biological explanations for and responses to madness / Philip Thomas -- The psychology of psychosis / Richard Bentall -- Sociological aspects of personality disorder / Nick Manning -- Sociological aspects of substance misuse / Michael Bloor and Alison Munro -- Social aspects of psychotropic medication / David Pilgrim, Anne Rogers and Jonathan Gabe -- Common mental health problems: primary care and health inequalities in the UK / Carolyn Chew-Graham -- Promoting mental health / Helen Herman -- Institutionalization and deinstitutionalization / Andrew Scull -- Action for change in the UK: thirty years of the user/survivor movement / Peter Campbell and Diana Rose -- Recovery in mental illness: the roots, meanings, and implementations of a'new' services movement / Ann McCranie -- Mental health problems, social exclusion and social inclusion: a UK perspective / Jenny Secker -- Social network influence in mental health and illness, service use and settings, and treatment outcomes / Bernice A. Pescosolido.
Includes bibliographical references and index.
Keywords: Mental health -- Case studies; Mental health -- Social aspects; Mental illness -- Case studies; Mental health; Mental disorders; Mental health services